Tinjauan Kerangka Kluckhohn terhadap Relasi Antar Pengurus Rumah Ibadah di Kota Singkawang - Akbar, Muhammad Fadhly; Rizki Rifaldy; Satrio Nurbantara; Adinda Putri Kartika; Nur Holifah Ihtisya Maharani; Juniar Dwi Inayati; Abdul Fatah (AN NUR: Jurnal Studi Islam, 2024)
Becoming the most tolerant city in 2023, the city of Singkawang is able to show an attitude that contains a narrative full of religious tolerance, especially regarding relations between places of worship. This research was conducted using Kuckhohn's theoretical approach to dissect the relationships between administrators of places of worship in the city of Singkawang. Researchers in this study used data through observations at places of worship and conducting interviews with administrators of places of worship from each religion. The results of the research were that there were good relations between administrators of places of worship. This can be seen from some of the habits and attitudes they show towards each other. Based on Kluckhohn's theoretical framework, good relations between administrators of places of worship in the city of Singkawang occur due to their similar orientation and reactions in viewing three basic problems in human life, namely the nature of life, the nature of time, and the nature of human relationships with others. They say the essence of life is good, so it needs to be maintained for now and the future. Because after all, humans will always depend on other humans to maintain the benefits of fellow humans as social creatures.